2013
DOI: 10.1093/oep/gpt025
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of welfare entry and exit amongst natives and immigrants

Abstract: This article studies welfare entry and exit in Germany and determines the relevance of state dependence for natives and immigrants. Based on dynamic multinomial logit estimations, we calculate transition matrices between three labour market states. We find that temporal persistence in welfare participation can mostly be explained by observed and unobserved characteristics. Immigrants appear to have a higher risk of welfare entry and a lower probability of welfare exit compared to natives. The results do not yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 40 publications
(44 reference statements)
2
29
0
Order By: Relevance
“…Several other studies in economics have used this approach recently, e.g., Geishecker and Siedler (2011), Wunder and Riphahn (2014) and Boll et al (2016) Using the same methods, we also investigated the impact of diabetes on changes in the type of work for those already employed, finding no evidence that diabetes leads to changes in the type of work. These results are also available on request.…”
Section: Duration Of Self-reported Diabetesmentioning
confidence: 99%
“…Several other studies in economics have used this approach recently, e.g., Geishecker and Siedler (2011), Wunder and Riphahn (2014) and Boll et al (2016) Using the same methods, we also investigated the impact of diabetes on changes in the type of work for those already employed, finding no evidence that diabetes leads to changes in the type of work. These results are also available on request.…”
Section: Duration Of Self-reported Diabetesmentioning
confidence: 99%
“…Survey data usually provide information on benefit receipt at the time of interview. Where this is the case, researchers have usually opted for a ‘point‐in‐time’ approach by modelling benefit transitions from one annual interview to the next, implicitly assuming that the transition probabilities remain unaffected by whether an individual received any payments in between those dates (Cappellari and Jenkins, ; Riphahn and Wunder, ; Königs, ; Wunder and Riphahn, ) . Administrative records by contrast often contain data on the total amount of benefits received during the calendar year but no information on the timing of receipt.…”
Section: Institutional Background and Datamentioning
confidence: 99%
“…The recent work on welfare benefit dynamics has primarily relied on estimation of dynamic discrete‐choice models to study state dependence in benefit receipt . Due to the limited availability of individual‐level data on welfare benefit receipt at shorter observation intervals much of the evidence on state dependence in welfare benefit receipt is based on annual data that come either from administrative sources (see Hansen and Lofstrom, , ; or Andrén and Andrén, for Sweden) or from household survey data (Cappellari and Jenkins, for Britain; Riphahn and Wunder, ; Wunder and Riphahn, and Königs, for Germany; Hansen et al ., for Canada). Notable exceptions are two U.S. studies based on monthly administrative data from California (Chay et al ., ) and four‐monthly survey data (Chay and Hyslop, ), and a study of transitions between Australian benefit programmes based on quarterly data (Gong, ).…”
mentioning
confidence: 99%
“…For example, a study for Germany found little evidence for state dependence in welfare dependency [11]. This suggests that incentive problems are not the only mechanisms behind poverty trap dynamics.…”
Section: Martin Biewenmentioning
confidence: 99%
“…The studies cited here cover specific time periods, some of which are more recent than others. Some use data up the middle of the first decade of the 2000s [4], [7], [9], [10], [11]; others use data from the 1990s or early 2000s [1], [2], [5], [6], [8], [12], [13] or even from the 1980s or earlier [3].…”
Section: Limitations and Gapsmentioning
confidence: 99%